Towards an Inclusive Village: Literacy and Education for People with Disabilities Through the Development of Grape Planting Techniques (Vitis Vinifera L) Taman Ayu Village - Herdiana, Herdiana; Andiana, Baiq Dewi Lita; Mappanganro, Nurlailah (Pascasarjana Universitas Mataram, 2024)
People with disabilities are identical to people who are disabled, weak, stupid and backward. People with disabilities are no longer seen as problematic people, by providing equal access and being inclusive for everyone in their society (168 169). Equal roles for people with disabilities are an important issue for the government. Recognition of equal rights for groups with disabilities, both in terms of education, employment opportunities and others. Community service activities carried out by Herdiana, et al. in Taman Ayu village, in 2023 became the main basis for empowering people with disabilities and knowledge for people with disabilities, especially in the equality garden by involving groups with disabilities. Taman Ayu Village, Gerung District, West Lombok Regency, West Nusa Tenggara (NTB) in the